The Conference of Parties - 27 (COP-27) Agreement As an Instrument of State Policy in Handling Deforestation: A Comparative Study of Sweden and Indonesian Governments - Mutawalli, Muhammad; Ayub, Zainal Amin; Maskun, Maskun; Napang, Marthen (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The climate crisis is a threat to countries in the world. One of the factors causing the climate crisis is deforestation. Indonesia as the third largest tropical forest country in the world certainly has an impact on the world's climate. Indonesia is a victim of deforestation, moreover reforestation of forest land does not match the rate of deforestation. This research is a normative legal study, using comparative, conceptual, and regulatory approaches. This study discusses the implementation of the Conference of Parties - 27 (COP-27 ) agreement as the basis for establishing policy instruments in Indonesia in dealing with deforestation and looks at Sweden as a comparison in handling deforestation through a policy instrument scheme. This study found that Sweden, through its green politics concept, was able to control the harvesting and utilization of forest products effectively. COP-27 has environmental control principles, one of which is the global net zero principle, namely the earth's temperature is no more than 1.5 degrees. it is hoped that the principles in COP-27 will guide the Indonesian government in making legal policy instruments for environmental management, especially handling deforestation. This research suggests that, like Sweden's green politics, Indonesia needs to present strategic policies through the Green Environmentally Concept policy through policy instruments, be it through laws and regulations, government regulations, or presidential regulations to the level of regional regulations.